Impact of low-dose computed tomography screening on lung cancer mortality among asbestos-exposed workers. (15th October 2018) - Barbone, Fabio; Barbiero, Fabiano; Belvedere, Ornella; Rosolen, Valentina; Giangreco, Manuela; Zanin, Tina; Pisa, Federica E; Meduri, Stefano; Follador, Alessandro; Grossi, Francesco; Fasola, Gianpiero
Abstract: Background: We previously showed that low-dose computed tomography (LDCT) screening in asbestos-exposed workers is effective in detecting lung cancer (LC) at an early stage. Here, we evaluate whether LDCT screening could reduce mortality from LC in such a high-risk population. Methods: Within a cohort of 2433 asbestos-exposed men enrolled in an Occupational Health surveillance programme, we compared mortality between the participants in the ATOM002 study (LDCT-P, N  =   926) and contemporary non-participants (LDCT-NP, N  =   1507). We estimated standardized mortality ratios for the LDCT-P and LDCT-NP populations using regional and national rates (SMR_FVG and SMR_ITA, respectively). We compared survival for all causes, all neoplasms, LC and malignant neoplasm of pleura (MNP) between LDCT-P and LDCT-NP using Cox proportional hazard models adjusted for age, smoking history, asbestos exposure level and comorbidities. Results: A reduction in mortality from LC was observed in the LDCT-P group compared with regional and national figures (SMR_FVG  =  0.55, 95% confidence interval (CI) 0.24-1.09; SMR_ITA  =  0.51, 95% CI 0.22-1.01); this was not the case for the LDCT-NP group (SMR_FVG  =  2.07, 95% CI 1.53-2.73; SMR_ITA  =  1.98, 95% CI 1.47-2.61). A strong reduction in LC mortality was observed for the LDCT-P compared with the LDCT-NP [hazard ratio (HR)  =  0.41, 95% CI 0.17-0.96]. Mortality was also reduced for all causes (HR  =  0.61, 95% CI 0.44-0.84), but not for all neoplasms (HR  =  0.97, 95% CI 0.62-1.50) and MNP (HR  =  0.86, 95% CI 0.31-2.41) within the LDCT-P population. Conclusions: In our cohort, participation in the LDCT screening study was associated with reduced mortality from LC. This finding supports the use of LDCT in surveillance programmes for asbestos-exposed workers.